1996
DOI: 10.1183/09031936.96.09081701
|View full text |Cite
|
Sign up to set email alerts
|

Early and late allergic reaction in the nose assessed by whole body plethysmography

Abstract: Physiological changes during late phase nasal responses after allergen challenge are difficult to establish and different criteria are used for the definition of a positive late phase nasal reaction. The objective of this study was to assess the value of whole body plethysmography in detecting changes in nasal airway resistance after allergen challenge and to suggest criteria for the definition of early and late phase nasal reactions.Nasal challenge with allergen was performed in 15 allergic patients. Nasal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
(16 reference statements)
1
8
0
Order By: Relevance
“…Cytology is useful for the late phase: an increase in the eosinophil count of >10% (10) indicated positive NPC results in nine of the 11 patients who had apparently tested negative according to clinical scores during the immediate phase. Nasal cytology is more sensitive than RNM or whole-body plethysmography (13) for detecting the late-phase response and is suitable for children because it is painless and ambulatory.…”
Section: Discussionmentioning
confidence: 99%
“…Cytology is useful for the late phase: an increase in the eosinophil count of >10% (10) indicated positive NPC results in nine of the 11 patients who had apparently tested negative according to clinical scores during the immediate phase. Nasal cytology is more sensitive than RNM or whole-body plethysmography (13) for detecting the late-phase response and is suitable for children because it is painless and ambulatory.…”
Section: Discussionmentioning
confidence: 99%
“…The authors recently performed a series of studies on repeated allergen challenges in the skin, nose and lower airways [ 40]. The effect of repeated allergen challenge in skin on early and especially on late allergic responses was first studied as it was speculated that repeated intradermal skin challenges might be a suitable model to study effects of repeated allergen exposure in the airways.…”
Section: Repeated Experimental Allergen Challengementioning
confidence: 99%
“…Because the authors were especially interested in late phase responses, a new, very sensitive technique was developed to record nasal reactions after allergen challenge. For this purpose a whole body plethysmography was used [ 6]. Large differences in response patterns to the repeated challenges were found in the nose and the skin, especially concerning the late response, varying from strongly enhanced responses to complete diminution of the response.…”
Section: Repeated Experimental Allergen Challengementioning
confidence: 99%
“…One of our objectives was to assess mucosal indices using nasal lavage techniques, which would have interfered with rhinomanometry measurements. De Bruin-Weller et al (20) described nasal LPR using whole body plethysmography , but found no correlation between the late phase data and measurements obtained using more common methods for nasal patency assessments, such as rhinomanometry and nasal peak ow. Others, however, have described a reduced nasal patency, assessed by rhinomanometry, 4 and 8 h after allergen challenge.…”
Section: Discussionmentioning
confidence: 99%